Co-Cultivations of Beauveria bassiana, Metarhizium anisopliae, and Trichoderma harzianum to Produce Bioactive Compounds for Application in Agriculture - Pauline Flores da Silva; Maicon Sérgio Nascimento dos Santos; Beatriz de Andrade Araújo; Bruno Douglas Kerber; Heloisa Alves Pinto de Oliveira; Jerson Vanderlei Carús Guedes; Marcio Antonio Mazutti; Marcus Vinícius Tres; Giovani Leone Zabot (Fermentation)
Regenerative agriculture aims to improve soil quality and restore soil biodiversity, re-establishing natural systems in agricultural areas. Among some strategies, it is important to reduce the use of chemical pesticides that affect the productive capacity of the soil and cause problems to the environment. Based on this necessity, we present a strategy of producing a single product with bioinsecticidal and biofungicidal effects by submerged co-cultivations and paired cultivations of Beauveria bassiana, Metarhizium anisopliae, and Trichoderma harzianum using different concentrations of glucose, sucrose, hydrolyzed animal protein (HAP), soybean meal hydrolysate plus organic phosphorus (SMH), and hydrolyzed feathers (HF) as renewable nutrients. The single cultivations and double and triple co-cultivations were carried out for 7 days at 28 °C in orbital agitation at 120 rpm. Most of the highest values of conidia were obtained in the treatments at the central point, in which (g L−1) glucose (20), sucrose (10), HAP (7.5), SMH (2.5), and HF (2.5) were used. The fermented broths were applied to the backs of adult bugs (Euschistus heros), which mostly provided 66–88% mortality. Beauveria bassiana + Metarhizium anisopliae showed approximately 70% inhibition against Sclerotinia sclerotiorum and Macrophomina phaseolina. As a way forward, this product demonstrated integrated bioactivities as insecticide and fungicide and can be optimized to substitute chemical pesticides that have negative impacts on the environment.